Controlled Human Hookworm Infection: Accelerating Human Hookworm Vaccine Development. (19th April 2018) - Diemert, David; Campbell, Doreen; Brelsford, Jill; Leasure, Caitlyn; Li, Guangzhao; Peng, Jin; Zumer, Maria; Younes, Naji; Bottazzi, Maria Elena; Mejia, Rojelio; Pritchard, David I; Hawdon, John M; et al.
Abstract: Background: Controlled human hookworm infection (CHHI) is a central component of a proposed hookworm vaccination-challenge model (HVCM) to test the efficacy of candidate vaccines. Critical to CHHI is the manufacture of Necator americanus infective larvae ( Na L3) according to current Good Manufacturing Practice (cGMP) and the determination of an inoculum of Na L3 that is safe and reliably induces patent infection. Methods: cGMP-grade Na L3 were produced for a phase 1 trial in 20 healthy, hookworm-naïve adults in the United States, who received either 25 or 50 Na L3. Participants were monitored for 12–18 weeks postinfection for safety, tolerability, and patency of N. americanus infection. Results: Both Na L3 doses were well tolerated. Early manifestations of infection included pruritus, pain, and papulovesicular rash at the application site. Gastrointestinal symptoms and eosinophilia appeared after week 4 postinfection. The 50 Na L3 inoculum induced patent N. americanus infection in 90% of this dose group. Conclusions: The inoculum of 50 Na L3 was well tolerated and consistently induced patent N. americanus infection suitable for future HVCM trials. Clinical Trials Registration: NCT01940757.